Applications of a Model of Endogenous Technical Change to US Industry Data - Rasmussen, Jon A. (Review of Economic Studies, 1973)
Journal Article Applications of a Model of Endogenous Technical Change to US Industry Data Get access Jon A. Rasmussen Jon A. Rasmussen Wesleyan University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 40, Issue 2, April 1973, Pages 225–238, https://doi.org/10.2307/2296649 Published: 01 April 1973